2003
DOI: 10.1038/sj.bmt.1704239
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pharmacological risk factors for acute graft-versus-host disease after paediatric bone marrow transplantation from matched-sibling or unrelated donors

Abstract: The aim of this study was to identify the risk factors for acute graft-versus-host disease (aGVHD) in children transplanted from a matched-sibling donor (MSD) or an unrelated donor (UD). In all, 87 children consecutively underwent allogeneic bone marrow transplantation (BMT) from MSD (n=36), and UD (n=51). GVHD prophylaxis included CsA alone (n=33) or with MTX (n=51). ATG was added in UD-BMT and thalassemic recipients. CsA whole-blood concentrations were measured by EMIT and the dosing regimen was monitored by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 35 publications
6
49
0
Order By: Relevance
“…Between 45 and 85% of children are reported to develop acute GVHD following MUD BMT, despite various combinations of prophylactic treatments. 32,33 Consistent with these data, 70% of the MUD BMT recipients in our series developed grade II or higher acute GVHD; however, it was transient and in most patients limited to the skin.…”
Section: Discussionsupporting
confidence: 86%
“…Between 45 and 85% of children are reported to develop acute GVHD following MUD BMT, despite various combinations of prophylactic treatments. 32,33 Consistent with these data, 70% of the MUD BMT recipients in our series developed grade II or higher acute GVHD; however, it was transient and in most patients limited to the skin.…”
Section: Discussionsupporting
confidence: 86%
“…This confirms the major role of antithymocyte globulin as part of GvHD prophylaxis in patients transplanted from unrelated donors. 11 We also report a low rate of TRM compared with other series where average TRM reaches 20-25%, 25,29,30,34 even though a large variability (7-45%) is possible. 27,35,38,39 Our results suggest that close monitoring of CsA therapy may permit a substantial reduction of GvHD-related mortality.…”
Section: Discussionmentioning
confidence: 89%
“…[8][9][10] It is now generally agreed that CsA trough blood concentration (TBC) is the pharmacokinetic parameter that best correlates with GvHD outcome. 11,12 Nevertheless, there are no data regarding specific values of CsA TBC to target to favor mild aGvHD without increasing the incidence of severe GvHD. Based on our previous experience, we have been performing therapeutic drug monitoring of CsA TBC combined with Bayesian dose adjustment, and targeting relatively low levels in leukemia patients.…”
Section: Introductionmentioning
confidence: 99%
“…And after conversion from intravenous administration to oral intake, C 5 was not available and only C 0 was measured. CsA concentrations were measured by radioimmunoassay based on monoclonal antibody (RIA) 9 until March 1997 (n ¼ 47), thereafter by fluorescence polarization immunoassay based on monoclonal antibody (M-FPIA) 10 using TDX system according to the manufacturer's instructions (Abbott Japan Co Ltd, Tokyo, Japan) until March 1999 (n ¼ 12).…”
Section: Drug Concentration Measurementsmentioning
confidence: 99%
“…1 Previous studies showed that low trough CsA concentration and reduction to less than 80% of the scheduled CsA dose were associated with the onset of grades II-IV acute GVHD. [2][3][4][5] However, these studies did not clarify fully whether low CsA concentrations, after the start of administration, are associated with the onset. Recent study reported that the incidence of grades II-IV acute GVHD was lower in the patients treated with twicedaily infusion of CsA than in those treated with the continuous infusion.…”
Section: Introductionmentioning
confidence: 99%